The structure of objects - Koslicki, Kathrin (Oxford : Oxford University Press, 2008)
The objects we encounter in ordinary life and scientific practice - cars, people, houses, molecules, etc. - have long been a fruitful source of perplexity for metaphysicians. This title gives an analysis of those material objects to which we take ourselves to be committed in our ordinary, scientifically informed discourse.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Object (Philosophy); Whole and parts (Philosophy); Structuralism